2019
DOI: 10.3390/ijerph16132316
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Cardiorespiratory Fitness between Chinese and Japanese Children and Adolescents

Abstract: Background: This study aimed to compare the difference in cardiorespiratory fitness between Chinese and Japanese children and adolescents. Methods: Participants comprised 9025 children and adolescents aged 7–18 years from China and Japan. Cardiorespiratory fitness (CRF) was measured by performance in the 20 m shuttle run test (20mSRT) and estimated maximal oxygen consumption (VO2max). Differences in CRF between countries were evaluated by t-tests. Centile curves for the 20mSRT and VO2max values were constructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In China, urban/rural status was considered when choosing schools because of the wide gap in economic development between urban and rural areas, whereas this factor was not taken into account in Japan. The detailed sampling methods are reported elsewhere [ 16 , 21 ]. Individual participants without psychiatric or physical disorders were recruited from the selected schools using stratified random cluster sampling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, urban/rural status was considered when choosing schools because of the wide gap in economic development between urban and rural areas, whereas this factor was not taken into account in Japan. The detailed sampling methods are reported elsewhere [ 16 , 21 ]. Individual participants without psychiatric or physical disorders were recruited from the selected schools using stratified random cluster sampling.…”
Section: Methodsmentioning
confidence: 99%
“…A meta-analysis suggested a large decline (−5.4 per decade) in long-distance running performance from 1964 to 2009 among children in China, but only a small decline (−1.2 per decade) among children in Japan [ 15 ]. It was also reported that cardiopulmonary endurance was higher among children and adolescents in Japan than in China [ 16 ]. Furthermore, a recent study showed that adolescents in Japan outperformed those in China in terms of aerobic capacity and muscular endurance but that adolescents in China performed better than those in Japan in terms of muscular strength [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“… 23 Chinese scholars demonstrated that CRF of children and adolescents was generally worse in China than in Japan. 24 In conclusion, the number of children with high waist circumference is increasing, while CRF level is decreasing. Based on the current situation, it is particularly important to explore the relationship between waist circumference and CRF.…”
Section: Introductionmentioning
confidence: 85%
“…For girls: Chinese, 13.7%; Japanese, 8.5%, respectively) and there was a high obesity rate (for boys: Chinese, 13.1%; Japanese, 4.3%, respectively. For girls: Chinese, 5.5%; Japanese, 1.2%, respectively); these factors were closely related [ 19 ].…”
Section: Introductionmentioning
confidence: 99%